Physico-chemical and Functional Properties of Myofibrillar Proteins of Fishes from Different Habitats - T.V., Sankar; Ramachandran, Dhanya; Mohan, Mukund; R., Anandan (Fishery Technology, 2025)
The conformational and functional characteristics of myofibrillar proteins of fishes from different habitats were investigated. Surface hydrophobicity and Ca2+ATPase activity of the MFP were higher in Mugil cephalus compared with the other fishes studied. Reactive sulphydryl groups were higher in Hypophthalmichthys molitrix. Lowest surface hydrophobicity (6.60) was recorded in MFP extracted from Oreochromis mossambicus. Solubility of MFP was higher for Lutjanus argentimaculatus. Solubility correlated well with the concentration of reactive sulphydryl groups and the surface hydrophobicity of the proteins. Viscosity was higher in H. molitrix and goes well with the reactive sulphydryl groups. Foam expansion and emulsion activity index was high in H. molitrix but foam volume stability and emulsion stability were lower in the MFP of this fish compared with the other fishes. Foam stability emulsion stability and gel strength were higher for Lethrinus lentjan. Protein conformation was found to have profound effect on the functional properties.